2018
DOI: 10.1111/ejh.13191
|View full text |Cite
|
Sign up to set email alerts
|

CD79B mutations in primary vitreoretinal lymphoma: Diagnostic and prognostic potential

Abstract: Objective Primary vitreoretinal lymphoma (PVRL) is a rare type of lymphoma wherein the lesions are limited to the eyes. PVRL is difficult to diagnose because of the challenges related to obtaining sufficient samples for biopsy. Moreover, PVRL has poor outcomes and often leads to the development of central nervous system (CNS) lesions during its course. Two studies recently reported that approximately 70%‐80% of patients with vitreoretinal lymphoma have MYD88L265P, which is frequently mutated in primary CNS lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 25 publications
2
51
2
Order By: Relevance
“…Among them, PVRL‐2 and PVRL‐4 showed early progression in the CNS within 2 years after treatment, whereas the others did not. Recently, it was reported that MYD88 L265P and mutations in the ITAM region of CD79B around Y196 were frequently detected in PVRL at rates of approximately 80% and 35%, respectively. As shown in Table 1, our PVRL cases had at least one of these mutations.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Among them, PVRL‐2 and PVRL‐4 showed early progression in the CNS within 2 years after treatment, whereas the others did not. Recently, it was reported that MYD88 L265P and mutations in the ITAM region of CD79B around Y196 were frequently detected in PVRL at rates of approximately 80% and 35%, respectively. As shown in Table 1, our PVRL cases had at least one of these mutations.…”
Section: Resultssupporting
confidence: 52%
“…Interestingly, 6 of 7 patients with vitreous DNA available for analysis had either MYD88 L265P or mutations in the ITAM region of CD79B . It was reported that MYD88 L265P and the mutations in CD79B were frequently detected in PVRL . However, these mutations were reported to be infrequent in GCB‐type DLBCL .…”
Section: Discussionmentioning
confidence: 38%
“…2,3,18, The highest prevalence of MYD88(L265P) is found in lymphoplasmacytic lymphoma/WM, with approximately 85% of the patients being affected. 18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In DLBCL, the prevalence of MYD88(L265P) is highest (range, 44% to 73%) in extranodal DLBCL, in immune-privileged sites, 96 such as primary DLBCL of the central nervous system 18,22,23,[86][87][88]96 and primary testicular lymphoma, 22,23,96,108 primary cutaneous DLBCL, leg type, 22,71,89-91 orbital/vitreoretinal DLBCL, 22,97,98 intravascular large B-cell lymphoma, 95 and primary breast DLBCL. 22,99 The high prevalence of MYD88(L265P) in extranodal site-specific lymphomas, lymphoplasmacytic lymphoma, and WM may provide an indication for the origin of these lymphomas.…”
Section: Prevalencementioning
confidence: 99%
“…15 Intriguingly, this genetic subgroup is linked to primary extranodal lymphomas, including lymphomas arising in the central nervous system (CNS), ocular vitreo-retina and testis, all considered 'immune-privileged' sites as they tolerate allografts and permit only selective entrance of immune cells. [16][17][18][19] Importantly, Wilson et al established that ABC DLBCL harboring mutations in CD79B, particularly those with concurrent MYD88 mutations, were highly responsive to treatment with ibrutinib, a selective Bruton's tyrosine kinase (BTK) inhibitor. 20 These observations suggest that (extranodal) lymphomas belonging to the MCD subtype could also be targeted by inhibition of BCR signaling.…”
mentioning
confidence: 99%